Peningkatan Kinerja Guru dalam Pengembangan Evaluasi Hasil Belajar melalui Supervisi Akademis Kepala Sekolah - Mujitahid, Ahmad (YASIN, 2022)
This research is about improving teacher performance through the academic supervision of the Principal, the results are very good. This was evident at the first meeting of the 6 teachers who were present at the time this research was carried out with an average score of ; 61.67% increased to 69.11% and in cycle 3 increased to 80.00%. From the analysis of the data above, the school principal's performance development through the school principal's academic supervision is effectively implemented in an effort to improve teacher performance, which means that the principal's coaching process is more successful and can improve teacher performance, especially at SD Negeri 46 Ampenan, Ampenan District, therefore it is hoped that the Principals can carry out coaching through academic supervision on an ongoing basis. The results of the research above show that improving teacher performance in the development of evaluating learning outcomes through the academic supervision of the school principal towards the desired change reaches 85% of its achievement, so the teacher's performance is said to be effective. Thus, the hypothesis proposed above can be accepted.